Enhanced differentiation of intraepithelial lymphocytes in the intestine of polymeric immunoglobulin receptor‐deficient mice. Issue 1 (26th June 2015) - Kato‐Nagaoka, Noriko; Shimada, Shin‐Ichiro; Yamakawa, Yoko; Tsujibe, Satoshi; Naito, Tomoaki; Setoyama, Hiromi; Watanabe, Yohei; Shida, Kan; Matsumoto, Satoshi; Nanno, Masanobu
Summary To clarify the effect of secretory IgA (sIgA) deficiency on gut homeostasis, we examined intraepithelial lymphocytes (IELs) in the small intestine (SI) of polymeric immunoglobulin receptor‐deficient (pIgR−/−) mice. The pIgR−/− mice exhibited the accumulation of CD8αβ+ T‐cell receptor (TCR)‐αβ+ IELs (CD8αβ+αβ‐IELs) after weaning, but no increase of CD8αβ+γδ‐IELs was detected in pIgR−/− TCR‐β−/− mice compared with pIgR+/+ TCR‐β−/− mice. When 5‐bromo‐2′‐deoxyuridine (BrdU) was given for 14 days, the proportion of BrdU‐labelled cells in SI‐IELs was not different between pIgR+/+ mice and pIgR−/− mice. However, the proportion of BrdU‐labelled CD8αβ+‐IELs became higher in pIgR−/− mice than pIgR+/+ mice 10 days after discontinuing BrdU‐labelling. Intravenously transferred splenic T cells migrated into the intraepithelial compartments of pIgR+/+ TCR‐β−/− mice and pIgR−/− TCR‐β−/− mice to a similar extent. In contrast, in the case of injection of immature bone marrow cells, CD8αβ+αβ‐IELs increased much more in the SI of pIgR−/− TCR‐β−/− mice than pIgR+/+ TCR‐β−/− mice 8 weeks after the transfer. αβ‐IELs from pIgR−/− mice could produce more interferon‐γ and interleukin‐17 than those of pIgR+/+ mice, and intestinal permeability tended to increase in the SI of pIgR−/− mice with aging. Taken together, these results indicate that activated CD8αβ+αβ‐IELs preferentially accumulate in pIgR−/− mice through the enhanced differentiation of immature haematopoietic precursor cells, which may subsequently result in the disruption of epithelial integrity.